Abdominal access techniques. Issue 2 (February 2021) - Hammer, Clare; Richardson, John
Abstract: This article discusses the variety of techniques available to gain safe exposure to intra-abdominal organs. In recent years there have been significant advances in these techniques with a move towards minimally invasive strategies as the gold standard of care. This article will discuss the various options available, including laparoscopy and traditional open access, as well as the use of robotics within abdominal surgery.